Contemporary English in the USA - Axelrod, Melissa; Scheibman, Joanne (International Journal of Language, Translation and Intercultural Communication, 2013)
Indigenous and immigrant speakers from a variety of linguistic and sociocultural backgrounds have in diff erent ways contributed to the development of presentday American English, as have the geographical and social dimensions of thecountry. This paper provides a survey of contemporary usage of American English by describing and illustrating linguistic features documented for social and regional groups in the United States. The focus on variation in pronunciation, grammar, and meaning in American English highlights the diversity of dialects and styles in the U.S. as well as the centrality of sociocultural identities to language use. We group examples of variation according to the social and geographical factors that these features have been associated with in the literature: region, age, ethnicity, and gender. We note though that patterns of linguistic usage differ both within and across communities, with particular features used by diff erent social groups for shifting purposes. The examples here provide a snapshot of the kinds of variation observed in contemporary American English as we move into the 21st century.